دور المجتمع المدني في حماية المال العام من جرائم الفساد والرشوة - شوقي, سمير (Université de M'sila, 2019)
- الملخص- تعمل الدول على مكافحة الفساد من خلال سلطاتها وأجهزتها الرسمية إضافة إلى تعاونها مع المجتمع المدني و وحتى القطاع الخاص، وقد أكدت التجارب الدولية في مجال مكافحة الفساد والرشوة، ضرورة إشراك المجتمع المدني في محاربة الظاهرة. إنّ العمل مع المجتمع المدني سيجعل من مكافحة الفساد تخطو من مرحلة الوعود السياسية إلى الواقع، و سوف يكون نجاح هيئات مكافحة الفساد محدودا دون دور للمجتمع المدني في تشكيل وتنفيذ أنشطة مكافحة الفساد والدفاع عن استقلالية الهيئات. لذلك حاولنا رصد بعض الجوانب المحيطة بعمل المجتمع المدني في مجال مكافحة الفساد، وأيضا تقديم بعض المقترحات الهادفة لتعزيز أدواره في ظل المستجدات التي ارتقت به إلى فاعل أساسي في صياغة ومراقبة وتتبع السياسات العمومية. Summary- Countries are working to combat corruption through their authorities and official bodies in addition to their cooperation with civil society and even the private sector. International experiences in combating corruption and bribery have confirmed the need to involve civil society in combating the phenomenon. Working with civil society will make the fight against corruption go from political promises to reality. The success of anticorruption agencies will be limited without the role of civil society in shaping and implementing anti-corruption activities and defending the independence of bodies. Unfortunately, the indicators of corruption in the Arab countries are the highest in the world while the growth rates are the lowest because corruption hinders development and the return of their revenues, so we tried to monitor some aspects surrounding the work of civil society in the fight against corruption and also to make some suggestions aimed at strengthening its roles in light of the developments Is an essential actor in the formulation, monitoring and tracking of public policies
Keywords: مكافحة الفساد، المجتمع المدني ،الرشوة، السياسات العمومية. ; Anti-Corruption, Civil Society, Bribery, Public Policies